2007
DOI: 10.1197/j.aem.2006.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Hospital Admission among Emergency Department Patients with Chronic Obstructive Pulmonary Disease Exacerbation

Abstract: Objectives: To determine the patient factors associated with hospital admission among adults who present to the emergency department (ED) with acute exacerbations of chronic obstructive pulmonary disease (COPD) and to determine whether admissions were concordant with recommendations in the Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines. Methods:The authors performed a prospective multicenter cohort study involving 29 EDs in the United States and Canada. By using a standard protocol, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
(25 reference statements)
1
21
3
Order By: Relevance
“…Some authors from the United States, such as Rowe et al 27 and Tsai et al, 28 reported higher admission rates (49.3 and 62%, respectively) than we did. The differences observed are most likely attributable to our cohort originating from primary care, where the average severity of the disease is lower.…”
Section: Discussioncontrasting
confidence: 39%
“…Some authors from the United States, such as Rowe et al 27 and Tsai et al, 28 reported higher admission rates (49.3 and 62%, respectively) than we did. The differences observed are most likely attributable to our cohort originating from primary care, where the average severity of the disease is lower.…”
Section: Discussioncontrasting
confidence: 39%
“…This percentage is twice as large as the overall hospitalization percentage for all ED visits made by patients aged Ն 45 years in the NC DETECT data (25.8%). Regarding subsequent hospital admissions, older age was associated with increased likelihood of hospital admission, 17 although in our study, the increased risk plateaued at ages 65 to 79 years. Again, similar to Watson et al, 16 we did not fi nd sex differences in subsequent hospital admission.…”
Section: Hospital Admissionscontrasting
confidence: 43%
“…Studies of this technology in the hospital setting have provided robust support for the routine use of NIV in patients with cardiogenic pulmonary edema and respiratory failure due to AECOPD. 5,12 NIV has been shown to decrease rates of intubation, improve physiologic parameters, and even decrease mortality in hospital. 6 Barriers to the widespread adoption of this treatment modality in the prehospital setting were largely due to the size, weight, and cost of older models; however, recent technological advances have led to increasing use.…”
Section: Discussionmentioning
confidence: 99%